2020
DOI: 10.25259/ijms_271_2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on radiologists

Abstract: COVID-19 pandemic is one of the biggest crises faced by health-care systems in the recent times. The aim of this study was to assess the impact of the COVID-19 pandemic on radiology workflow, working pattern, training and continuing professional development (CPD) activities, as well as personal well-being of the radiologists during the pandemic. Material and Methods: Questionnaire designed to gather the opinions regarding the impact of the COVID-19 pandemic was distributed to radiologists throughout the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Radiologists who spend more time at their workstations have a higher prevalence of musculoskeletal problems [ 24 ]; similar results were found in our investigation. Most of the study participants reviewed medical images on computers for an average of 7–9 h per day, which is comparable with a prior study on radiologists [ 31 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Radiologists who spend more time at their workstations have a higher prevalence of musculoskeletal problems [ 24 ]; similar results were found in our investigation. Most of the study participants reviewed medical images on computers for an average of 7–9 h per day, which is comparable with a prior study on radiologists [ 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…Regarding the impact of COVID-19 pandemic, it has had apparent effect on the radiologists everywhere. A previous study reported that during the pandemic, the number of radiologists in the office decreased dramatically as more people chose to work from home [ 31 ]. Possibly because of the greater severity of other organ system manifestations of COVID-19, the musculoskeletal (MSK) manifestations of this virus have not been completely reported [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Multiple studies from all over the world have shown that HCWs suffer from increased stress, anxiety, depression, insomnia, and other psychological problems because of working in COVID-19 wards. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The present study is being reported from a dedicated COVID-19 hospital in Punjab in North India to assess the perceived stress among doctors and find its association with working hours, age, designation, and other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Performing ultrasonography not only requires specialized equipment but also the availability of an expert round the clock. COVID-19 pandemic had a widespread impact on radiologists, increasing their workload and exposure to the virus leading to an alarming rise in sickness absenteeism [ 2 ]. In certain parts of the world, this led to delays in appointments, long waiting times for imaging studies, and delays in diagnosis and initiation of treatment, significantly affecting the patient care.…”
Section: Introductionmentioning
confidence: 99%